2009
DOI: 10.1159/000234814
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after Lithium Augmentation in Unipolar Depression: Focus on HPA System Activity

Abstract: Background: Lithium augmentation is a first-line strategy for depressed patients resistant to antidepressive therapy, but little is known about patients’ subsequent long-term course or outcome predictors. We investigated long-term outcomes of unipolar depressed patients who had participated in a study on the effects of lithium augmentation on the hypothalamic-pituitary-adrenocortical system using the combined dexamethasone/corticotrophin-releasing hormone (DEX/CRH) test. Methods: Twelve to 28 months (mean 18.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…One assumption that contradicts available evidence is the assumption that relapse rates following augmentation or combination therapy would be the same as following first-line treatment. 96 However, this assumption can be regarded as conservative as any bias would be directed against escitalopram. The source of effectiveness data was clearly described for patients at all 54 stages of the model pathways.…”
Section: Critiquementioning
confidence: 99%
“…One assumption that contradicts available evidence is the assumption that relapse rates following augmentation or combination therapy would be the same as following first-line treatment. 96 However, this assumption can be regarded as conservative as any bias would be directed against escitalopram. The source of effectiveness data was clearly described for patients at all 54 stages of the model pathways.…”
Section: Critiquementioning
confidence: 99%
“…A number of investigations in depressed patients have highlighted a pattern of diminished Dex/CRH test cortisol response over time as a correlate or predictor of clinical improvement during antidepressant therapy (Sagud et al 2002; Schule et al 2006), with persisting patterns of elevated cortisol response to the test despite clinical remission predicting enhanced risk for future relapse. Very few have found increased cortisol reactivity in depressed patients associated with chronic pharmacotherapy, though two studies reported increased cortisol reactivity following lithium augmentation of antidepressants (Adli et al 2009; Bschor et al 2002). …”
Section: Discussionmentioning
confidence: 99%